2019
DOI: 10.1016/j.molimm.2019.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Salt bridge-forming residues positioned over viral peptides presented by MHC class I impacts T-cell recognition in a binding-dependent manner

Abstract: A B S T R A C TThe viral peptides presentation by major histocompatibility complex class I (MHC I) molecules play a pivotal role in T-cell recognition and the subsequent virus clearance. This process is delicately adjusted by the variant residues of MHC I, especially the residues in the peptide binding groove (PBG). In a series of MHC I molecules, a salt bridge is formed above the N-terminus of the peptides. However, the potential impact of the salt bridge on peptide binding and T-cell receptor (TCR) recogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…We observed salt bridge‐forming residues positioned over the viral epitopes in three of the five complexes, as well as continuous hydrogen bonding between epitopes and HLA chains maintained throughout the simulation in all complexes (Figure 1B,C). Mutations in salt bridge‐forming amino acids have been shown to weaken TCR recognition of MHC class I‐antigen complexes 19 . Also, the continuous formation of a set of hydrogen bonds between the MHC molecules and epitopes indicates an accommodating nature of the HLA chains to bind epitopes within the groove between the two helices 20 .…”
Section: Resultsmentioning
confidence: 66%
“…We observed salt bridge‐forming residues positioned over the viral epitopes in three of the five complexes, as well as continuous hydrogen bonding between epitopes and HLA chains maintained throughout the simulation in all complexes (Figure 1B,C). Mutations in salt bridge‐forming amino acids have been shown to weaken TCR recognition of MHC class I‐antigen complexes 19 . Also, the continuous formation of a set of hydrogen bonds between the MHC molecules and epitopes indicates an accommodating nature of the HLA chains to bind epitopes within the groove between the two helices 20 .…”
Section: Resultsmentioning
confidence: 66%
“…3A ; Figure S13D, Supplementary Material ). Comparative MD simulations of GLKEGIPAL and GVKEGIPAL peptides showed that while both formed similar hydrogen bonds, V2 was closer to the beta-floor sheet than L2, consistent with tighter binding in the B pocket and improved peptide stability ( Figures S13E and S13F, Supplementary Material ) ( 43 , 44 ). Furthermore, comparison of the relative movements of p66 residues indicated that N66 was more mobile with L2 but more stable with V2 present; by contrast, K66 made stable interactions with either L2 or V2 (Fig.…”
Section: Resultsmentioning
confidence: 76%
“…Homologous epitopes from other coronaviruses have the potential to elicit cross T cell responses to SARS-CoV-2 infection, so we also summarized the structures of HLA complexes loaded with SARS-CoV-derived peptides (Table 1 and Fig. 2A) [60,[77][78][79][80][81]. Three peptides are based on the HLA-A*0201-restricted type, and there is one for each of the other HLA alleles, i.e., HLA-A*2402, HLA-B*1501, HLA-A*1101, and HLA-B*4001.…”
Section: Potential For Cross-t Cell Recognition Of Sars-cov-2 and Sar...mentioning
confidence: 99%